Online feature trend monitoring and signal pattern clustering in milling process - Wang, Yu. (2010)
Data mining is a powerful technology used in the manufacturing industries to discovery useful information. Data mining technology could be integrated with computer integrated manufacturing system in order to analyze the data of the real situation of the manufacturing process. Clustering is one form of unsupervised learning used in data mining. There are a number of applications in a wide variety of area such as pattern recognition, image processing, automatic control, communication, and bio-information.